(untitled) (Damascus University Journal of arts and humanities sciences, 2024)
Recent technological developments affected all areas of life, especially educational and academic education, so the Syrian virtual education sites appeared, despite the circumstances that Syria went through, so it was necessary to keep pace with these developments and keep pace with the course of progress, so the Syrian Virtual University and the Syrian Virtual School appeared, hence the importance of the study The current situation is that students can complete their studies via the network from kindergarten to specialization at the university, and given that virtual education takes place via the network, therefore it needs to create its own website and make it available Everything related to the school or university through this site, and here this research will serve as a test to determine the extent to which these sites depend on the scientific foundations in their construction. The site, its content, the general structure, its technical standards, and the libraries associated with it. Here, the study reached a set of results, the most important of which was that all sites share the advantage of ease of access to the site, as well as that the languages ​​supported by the sites of Syrian virtual education institutions are Arabic and English the study made some recommendations for the development of Syrian virtual education sites, the most important of which was defining a clear and explicit icon through the site, once you click on it, it takes us to a link associated with it, and encourages sites (the study sample) to apply advanced search, and the need to support the feature of the possibility of sorting the results of the search process.